Context-aware mobile app for the multidimensional assessment of the elderly, - Berrocal, J. (2019)
Rural areas in Europe are presenting a decreasing population density and an increasing age index. These elders usually present multiple diseases that require complex tools to identify the exact cares that they need. Currently, different frameworks can evaluate their functional status and identify the required cares to maintain their Quality of Life, together with the associated cost to the health system. Nevertheless, these frameworks are usually questionnaires that have to be performed by already overloaded professionals. In this paper, we make use of mobile technologies to build a system capable of monitoring the activities of the elderly and analysing these data to assess their functional status. The experiments carried out show us that it correctly evaluates these patients and reduces the effort required by health professionals.